1995
DOI: 10.1177/096032719501400201
|View full text |Cite
|
Sign up to set email alerts
|

Protection against inhalation toxicity of ricin and abrin by immunisation

Abstract: 1 Abrin and ricin are highly toxic plant proteins which are very similar in structure and function and inhibit protein synthesis in eukaryotes. 2 Rats have been immunised against either toxin using formaldehyde-toxoids by three subcutaneous injections at intervals of 3 weeks. For abrin, serum titres in 14 out of 15 rats were raised to between 1 : 12800 and 1 : 51200 after two injections, 6 weeks from the start of the experiment. Titres of between 1 : 256 and 1 : 1024 were also measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…vaccines protect mice from lethal ricin challenges. However, when aerosolized ricin was delivered to the vaccinated mice they still suffered significant lung damage [ 7,28 ]. Intranasal or intratracheal instillation of the toxoid induced good systemic immunity but failed to activate an adequate local response to protect the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…vaccines protect mice from lethal ricin challenges. However, when aerosolized ricin was delivered to the vaccinated mice they still suffered significant lung damage [ 7,28 ]. Intranasal or intratracheal instillation of the toxoid induced good systemic immunity but failed to activate an adequate local response to protect the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of small amounts of ricin aerosol can rapidly and irreversibly damage cells of the respiratory tract, leading to severe pulmonary incapacitation or death (3,12). Currently, there is no approved antidote, vaccine, or other specific medical treatment option for ricin exposure.…”
mentioning
confidence: 99%
“…Compared with A chain subunit, conventional toxoid preparation via protein denaturation has significant shortfalls that can lead to inadequate vaccine potency and poor quality control. 4,5,24 ATB is a galactose-specific lectin and can bind to cell surface glycosylated receptors and promote the entry of the ATA into the cytosol, which means that ATB is essential for the toxicity of AT. Meanwhile, previous studies also have demonstrated that B chain of toxins can exhibit both antigenic and adjuvant activity.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics make AT a choice for a suitable assassination weapon or a biological warfare agent . 3 Toxin poisoning usually can be prevented by vaccination with toxoid, 4,5 or by passive administration with antibodies in experimental animals. 2,6 Both procedures are effective in the prophylaxis or therapy of toxin poisoning in mice.…”
Section: Introductionmentioning
confidence: 99%